THE INFLUENCE OF THE PRODUCTION PROCESS AND QUALITY CONTROL ON THE QUALITY OF BANANA CHIP PRODUCTS AT ASKHA JAYA CHIP SHOP - Sinta Ariska; Vonny Tiara Narundana (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Currently, the MSME area in the country is experiencing a quite challenging atmosphere amid the change of business areas that continue to become complex. In a tight economic competition like today, industry actors are required to sort out several options, one of which is prioritizing quality to achieve a wider market share, one of which is at the Askha Jaya Banana Chip Store. The challenge that takes place in the Askha Jaya Banana Chips business is that there is still a process of creating manual methods, and the packaging problems that exist are also still very limited is by using hands alias manual, so that there are still often errors or defective objects or bad objects that take place after the production process. Process means the methods, tactics, and mechanisms in which current resources, hardware, materials, and assets are thoroughly transformed to achieve results. Quality control is a mechanism and structured exercises / activities carried out to achieve, follow and work on the nature of goods and services in accordance with predetermined guidelines and can meet consumer loyalty. The purpose of this research is to recognize the influence of variables on the Askha Jaya Banana Chip Store. This research method uses quantitative descriptive research, with a sample of 35. Then the information is processed using SPSS version 22. The results of the research show that the production process and quality control together have a positive and significant effect on product quality at the Askha Jaya Banana Chip Store.